Bayesian Belief Network Analysis for Chinese Off-Site Manufacturing Risk - Lin Zhang; Yanan Hou (Buildings)
The construction industry continues to face challenges such as increased costs, time overruns, and low quality. Off-site construction (OSC) methods are increasingly being adopted as alternatives to traditional construction practices to address these issues, with off-site manufacturing (OSM) representing a key difference in construction methods. However, existing studies have largely neglected the systematic evaluation of OSM risks on quality, cost, and delivery (QCD) outcomes, leaving a significant gap in understanding the complex interdependencies among risk factors. To improve risk management in OSC projects, it is crucial to evaluate the impact of OSM risks on QCD outcomes. This study applies the Bayesian Belief Network (BBN) method to develop an evaluation model that measures the impact of OSM risks on QCD outcomes in OSC projects. The results identify 12 significant risk factors affecting QCD outcomes in OSC projects. Five key risk groups were identified as critical for managing OSM risks. This approach provides a systematic framework for managing OSM risks and optimizing OSC practices in China.